Quadriceps Femoral Angle (Q Angle) Variations in Knee Osteoarthritis Patients - Nadia Anwer, Naila Manzoor, Qurba Kiran, Maryam Saleem, Syeda Areeba Fatima, Azka Rehan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Osteoarthritis is a degenerative disease most commonly occur in females, aged and obese population. Knee osteoarthritis is most common. Repetitive stress or some trauma to joint or some genetic disorder may be the cause of osteoarthritis. Q angle is the quantifying value between patellar angle and quadriceps. There is valuable rise in the value of Q angle in knee OA patients because of increased medial tibial torsion. Standard value of Q angle is 17 for females and 14 for males. Objectives: To find out the variations of value of Q angle in knee OA. To find how BMI, age, gender affects the value of Q angle? Is there any effect of increased value of Q angle on foot arches? Materials and Methods: This study is a cross sectional study that has been conducted from December 2015 to June 2016. Data from 200 subjects was collected that had knee osteoarthritis (male and females) of different era. The data was collected from hospitals of Rawalpindi, Islamabad and Wah cantt. With the help of self created questionnaire. Different measuring devices including goniometer for measuring q angle measuring tape for sit to stand navicular drop test, are used weighing machine for weight measurement. Further analysis on collected data was made through SPPS.. Results: The study results showed the significant increment in value of Q angle was linked to weight and gender of the subjects. Value of Q angle was higher for overweight and obese females. Increased BMI was linked to increased risk of knee osteoarthritis. Chi-square test with cross tabulation was applied for the association of osteoarthritis and Q angle which were categorized in to 3. Category 1 was ranged from 14-20, category 2 was ranged from 20.1 to 25 and category 3 was ranged from 25.1 to 30 degrees. Chi square test results have shown p value is less than 0.005. This value is significant. Conclusion: The study concluded there was a marked rise in Q-angle in patient with knee OA who were obese ,overweight as compare to the normal BMI.OBESE PERSONS are prone to knee OA. The obese women normally have increased Q angle. Over-pronated feet or different position of foot also puts extra strain on the Q angle because of massive internal rotation of the tibia. Keywords: Osteoarthritis, Q angle